The vanishing at Castle Moreau [large type] - Wright, Jaime Jo (Thorndike Press large print Christian fiction series., 2023)
"In 1865, orphaned Daisy Francois takes a position as housemaid at a midwestern Wisconsin castle and finds that the reclusive and eccentric Gothic authoress inside hides more than the harrowing tales in her novels. With women disappearing from the area and a legend that seems to parallel these eerie circumstances, Daisy is thrust into a web that may threaten to steal her sanity, if not her life. In the present day, Cleo Clemmons is hired by the grandson of American aristocratic family the Tremblays to help his matriarchal grandmother face her hoarding in the dilapidated Castle Moreau. But when Cleo uncovers more than just the woman's stashes of collectibles, a century-old mystery of disappearance, insanity, and the dust of the old castle's curse threatens to rise again, and this time, leave no one alive to tell its sordid tale."--